GAGASAN HASAN LANGGULUNG TENTANG PENDIDIKAN ISLAM - Nurotun Mumtahanah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2011)
Abstract: Hasan Langgulung offers Islamization ideas of knowledge that developed by assimilation into the Islamization of the adaptatif curriculum (not adoptif) and accommodating with the beginning of the Islamization of education goals. According to him, the goal of Islamic education can be achieved by teaching certain knowledge. Not only by teaching that usually called knowledge of Islam but all kinds of sciences such as mathematics, biology, economics, and others. Without the Islamization of the goal, then the Islamization of subjects will be in vain. Islamization of the curriculum is intended to bring Muslim personalities and nuances of Islamic subjects. Islamization of science that developed into the Islamization of the curriculum is intended as a solution. Thus, dichotomous way of thinking as happens in Indonesia will soon to expire and switch to new ways of thinking, thinking that the Islamic religion does not distinguish between science and general knowledge to the next could follow the development of science without letting go of old values that are ensensial, nice and steady, and oriented towards transcendental values